Leader Propagation Characteristics Under Positive Lightning Impulse Voltages - Lei Jia; Song Zhang; Lu Qu; Yongxiang Cai; Huaifei Chen; Xiaobing Xiao; Ruihan Qi; Minchuan Liao; Jian Hu (IEEE Access)
Lightning strikes on transmission lines often generate overvoltage, which is the primary reason for insulator string flashover. This overvoltage, with a rapid rise time of just a few microseconds, causes leader propagation characteristics to differ significantly from those under an impulse with a slower rise time. However, most existing studies focus on leader behavior under slow-rise-time impulses, like switching impulse voltage, while research on fast-rise-time impulses remains limited. To address this gap, this study conducted a discharge experiment using a 5 m air gap under lightning impulse voltage in a lab setting. Voltage, current, and high-speed images were recorded simultaneously. The results revealed how leader velocity and charge per unit length relate to the leader’s position and voltage amplitude. When compared to switching impulse voltage, these characteristics were found to be ten times greater under lightning impulse voltage. The study also examined the leader’s branching behavior, including the number of branches and the spatial distribution of bifurcation points. It explored how voltage amplitude affects these traits, showing that higher voltage increases the likelihood of branching, with three or four branches becoming more common. Additionally, the research analyzed the leader’s attachment points and, for the first time, observed two attachment points occurring simultaneously. These findings enhance our understanding of how leaders behave dynamically under fast-rise-time impulse voltage.